ETUDE PRELIMINAIRE DE L’EFFICACITE DU CITRON VERT (CITRUS AURANTIFOLIA, RUTACEAE) DANS LA LUTTE CONTRE LA NUISANCE SIMULIDIENNE A PETIT-GARANGO ET ALLANGBA-KONANKRO, VILLAGES RIVERAINS DE LA MARAHOUÉ, DANS LA COMMUNE DE BOUAFLÉ, CÔTE D’IVOIRE - Grégoire, Yapi Yapi; Drissa, Coulibaly; François, Traore Dipomin; Emmanuel, Tia; Anne-Marie, Boby Ouassa; Marcel, Boka Ohoukou; Mahama, Toure; Alphonse, Kadjo Kouamé (European Scientific Journal, ESJ, 2014)
Entomological, parasitological and anthropological studies (surveys CAP: “knowledge, Attitudes and practices”) have been undertaken to assess blackflies nuisance and test the effectiveness of lemon (Citrus aurantifolia, Rutaceae) on the reduction of the nuisance caused by Blackflies. The anthropological investigation showed that: • Petit-Garango and Allangba-Konankro populations are heavily bitten by Blackflies and young people are most vulnerable to the disease; • Blackflies are abundant in rainy seasons; • agricultural activities are highly disturbed by the blackflies aggressiveness; • skin lesions are due to blackfly bites; • to protect against the nuisance activity, most of the people use appropriate clothing (pants and long-sleeved shirts), industrial or natural products. The work done by the use of lemon as natural repellent has shown that the fruit juice ensures 89.3% protection against blackfly bites. The results obtained with the lemon juice are encouraging. The final objective is to obtain 100% reduction. To reach this goal, we need to extract the active ingredient in lemon, make it into of ointment, and then test it.